Shape Memory Alloy Micro-Actuator for Handling of Head Gimbal Assembly - Prapaipittayakhun, K.; Srituravanich, W.; Pimpin, A. (Applied Science and Engineering Progress, 2013)
This study proposes a methodology to design a shape memory alloy micro-actuator as a new handling device of Head Gimbal Assembly (HGA). The actuator consists of several finger-like Nitinol-and-Polyimide bimorph beams that are able to deflect at high temperature due to thermally induced strain mismatch between these two materials. To design the geometry of micro-actuator, various beam dimensions including lengths, widths and thicknesses are evaluated using ANSYS program. Furthermore, the contact force between micro-actuator and HGA is also studied. The simulation results suggest the feasibility of using the proposed micro-actuator for HGA handling application